Associations between exercise and university students’ depression during the COVID-19 pandemic and lockdown: the mediating role of relative deprivation and subjective exercise experience - Chao Chen; Jie Ma; Jinzhuang Song; Chuang Yan; Minghao Yan (BMC Psychology)
Abstract Background The COVID-19 pandemic has profoundly impacted daily life globally since its emergence in early 2020. University students experiencing university lockdown during the COVID-19 pandemic may exhibit both horizontal relative deprivation (HRD) and vertical relative deprivation (VRD). Furthermore, as a well-established determinant of depression, relative deprivation (RD) warrants further investigation to determine whether it is associated with exercise, which requires more conclusive evidence. Currently, the available evidence is insufficient to draw firm conclusions on the relationships between student exercise and depression, RD and subjective exercise experience (SEE). Consequently, this context necessitates a critical re-examination of the exercise-depression relationship and clarification of its underlying mechanistic pathways. Methods Analysis of exercise-depression associations in two cross-sectional assessments during COVID-19 pandemic and lockdown was undertaken. In the first wave of data collection, we implemented a simple random sampling to recruit participants from five universities in Hebei Province. In accordance with the Beck Depression Inventory-II criteria, participants who scored ≥ 14 (indicating at least mild depression) were selected for inclusion in this study. After completing the baseline screening, a total of 915 eligible students were enrolled and proceeded to participate in the second-stage investigation. Key measures included the physical activity rating (PAR), RD, and SEE, allowing for a comprehensive analysis of exercise-depression associations. For the statistical analysis, descriptive statistics, correlation analysis, regression analysis, and mediation analysis were employed. We assessed the mediation effects using Baron and Kenny’s (1986) causal steps approach, with bootstrap sampling (5,000 iterations) to examine the statistical significance of indirect effects. Results The finding suggests that exercise was positively associated with SEE (β = 0.512, p < 0.01), which in turn was negatively associated with depression (β = -0.368, p < 0.01). SEE showed a significant negative association with RD (β = -0.477, p < 0.01), and lower RD was in turn associated with reduced depressive symptoms (β = 0.506, p < 0.01). Significant differences in exercise intensity, duration, and frequency were observed across depression levels (p < 0.05). A significant negative association was observed between exercise frequency and mild-to-moderate depression levels (p < 0.05). SEE showed significant negative association with both mild and moderate depression levels (P < 0.05). Conclusions The findings suggest that despite the profound impact of the COVID-19 pandemic and lockdown, exercise maintained a robust association with the alleviation of depressive symptoms. SEE serve as a key factor in generating positive emotions and reducing RD, which in turn contributes to lower levels of depression. Exercise intensity and frequency serving as important factors of symptom alleviation. Exercise frequency demonstrates a significant association with RD, which appears to alleviate depressive symptoms. To optimize the depression-alleviating benefits of exercise, students should engage in moderate exercise to avoid excessive fatigue while maintaining positive exercise experiences.